2021
DOI: 10.1371/journal.pone.0252241
|View full text |Cite
|
Sign up to set email alerts
|

Medical service quality, patient satisfaction and intent to revisit: Case study of public hub hospitals in the Republic of Korea

Abstract: This study aimed to construct and test structural equation modeling of the causal relationship between quality of healthcare, patient satisfaction, and intent to revisit perceived by patients using regional hub public hospitals. In this study, data of 2,951 outpatients and 3,135 inpatients were collected using the “2018 Regional Hub Public Hospital Operational Evaluation.” A structural equation model was used to understand the relationship between patient satisfaction and intent to revisit, and bootstrap analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
5
7
0
3
Order By: Relevance
“…How patients experienced quality was, in particular, associated with good communication, as well as perceived support from nurses and the nurses' attitude towards them. This finding is also in line with Woo and Choi [8], who found that the friendliness and consideration of the healthcare staff were the most important quality factors, as well as Ye et al [9], who claimed that doctor and nurse communication was the most significant driver for patients' experience of care.…”
Section: Introductionsupporting
confidence: 85%
“…How patients experienced quality was, in particular, associated with good communication, as well as perceived support from nurses and the nurses' attitude towards them. This finding is also in line with Woo and Choi [8], who found that the friendliness and consideration of the healthcare staff were the most important quality factors, as well as Ye et al [9], who claimed that doctor and nurse communication was the most significant driver for patients' experience of care.…”
Section: Introductionsupporting
confidence: 85%
“…Therefore, patient overall satisfaction with this factor was not high. The listening and sharing of information by medical staff had a potent effect on patient satisfaction, even higher than kindness and consideration, because outpatients would leave the hospital just after completing the examination and treatment, which means they had fewer opportunities to communicate with medical employees than the inpatients did [ 48 ]. In addition, pharmacy staff might have tired facial expressions when working with intense stress and receiving many patients, which might make patients feel that they do not care about their health.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of physician practice and hospital environment also has a significant impact on outpatient revisit intent, while for inpatients, physician practice and the kindness of medical staff directly influence revisit intent. Overall, delivering high-quality medical services and genuine patient care in all departments is essential for enhancing satisfaction and encouraging return visits from patients [ 21 ] as indicated by Woo and Choi.…”
Section: Reviewmentioning
confidence: 99%